Impact of Infrastructural Development on Economic Growth in Selected African Countries - Valentine Anim, Chibueze; O. Ishioro, Bernard (SMARTINDO, 2025)
Purpose - This study examines the impact of infrastructural development on economic growth in selected African countries, with a focus on key indicators such as electricity consumption, mobile cellular subscriptions, and access to clean water.. Design/methodology/approach - Using annual panel data from 1990 to 2023 for fifteen African countries, the study employs fixed effects, random effects, and dynamic ordinary least squares (DOLS) estimation techniques. Control variables include foreign direct investment, exchange rate, and inflation. Panel unit root and cointegration tests were conducted to validate the robustness of the models. Originality - The study offers updated empirical evidence on the infrastructure-growth nexus in Africa by using recent data and a broader set of infrastructure indicators. It also contributes to existing literature by employing dynamic panel modeling techniques to better capture long-run relationships. Findings and Discussion - The results reveal that electricity consumption, mobile cellular subscriptions, and access to clean water have statistically insignificant and negative effects on economic growth. In contrast, foreign direct investment has a positive and significant impact. These findings suggest that the current state and management of infrastructure in the selected African countries may not yet support growth-enhancing outcomes, potentially due to inefficiencies, inadequate access, or policy shortcomings. Conclusion - Infrastructure development, as currently implemented in the selected African countries, does not significantly promote economic growth. The study recommends that African governments reform infrastructure-related policies, improve service delivery, and ensure investments translate into economic outcomes through better governance and regulatory frameworks.